Nosotras somos oprimidas, esposas de obreros: mujeres y política en Río Blanco - Gerardo Necoechea (Estudios sobre las Culturas Contemporáneas)
Chronicle of the experience of wives of textile workers in a factory in Rfo Blanco in a union movement which lead to the independent formation of an association considering them as a group.